TATA KELOLA SANGGAR RANAH SAIYO DI NAGARI PAUH KABUPATEN PASAMAN (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2026)
This study aims to describe the management of Sanggar Ranah Saiyo in Nagari Pauh, Pasaman Regency. The focus of the research is directed at how the organizational management system is implemented in an effort to maintain the existence and development of the studio. The research method used is a descriptive qualitative approach, with data collection techniques including observation, interviews, literature study, and documentation. The main informants in this study are the leader of Sanggar Ranah Saiyo along with other management members. The results of the study indicate that the management of Sanggar Ranah Saiyo is carried out through five management functions, namely governance, planning, organizing, actuating, and controlling. This studio has a clear organizational structure and a well-established coordination system among its members. Sanggar Ranah Saiyo utilizes social media (Instagram) as its primary promotional tool, establishes partnerships with wedding organizers and event planners, and performs various traditional Minangkabau dances in cultural activities as well as government events. These strategies contribute positively to increasing the studio’s popularity and service demand. This study is expected to serve as a reference for students, art practitioners, and studio managers in developing effective management for the sustainability of traditional arts.